Investigating Vocational High School Instructors’ Views on Mobile Learning in the "Tourism English Conversation" Course - Wang, Yu-Ju; Liu, Da-Wei (Technium Education and Humanities, 2024)
This research delved into the perspectives of English teachers in vocational high schools towards mobile learning (m-learning) in the "Tourism English Conversation" course. It involved interviews with eleven teachers from public vocational high schools in Kaohsiung City, Taiwan. These interviews explored various facets of m-learning, such as teachers’ knowledge of mobile devices and apps, the widespread use of the Internet and mobile devices, instructional materials, and its impact on students’ learning duration and concentration. The study focused on three aspects of mobile learning: its acceptance, teachers’ readiness to adopt it, and the challenges they face in shifting from traditional to mobile teaching methods. Findings revealed a positive reception towards m-learning, particularly during the COVID-19 pandemic when traditional classroom teaching was impossible. Nonetheless, the effective implementation of m-learning was influenced by teachers’ familiarity with the technology, student motivation, the availability of relevant instructional materials, and the pressures associated with teaching in this new format.